Drivers of respiratory health care demand in Acre state, Brazilian Amazon: a cross-sectional study - Thiago Morello; Aldo Santos Lima; Rubicleis Gomes da Silva (BMC, 2022)
Abstract Background The scarce knowledge about the drivers of demand for respiratory health care in the Brazilian Amazon, where the gap of human and physical health care resources is wide, is expanded with two surveys conducted in the west of the region, in Acre state. Potential drivers, informed by a review of twelve recent papers, were classified into seven categories capturing the individual, household, community and macroeconomic dimensions. Methods Quantitative field surveys were conducted in 2017 and 2019 based on coupled conglomerate-quota randomization sampling. Adults responded about their own health or their children's health. The probability of seeking physician care for the latest episode of respiratory illness or dry cough was analysed with multiple nonlinear regressions, having as covariates the potential predictors informed by the literature. Results The propensity to seek health care and to purchase medication was larger for children. Influenza-like illness (Despite the exact diagnostic stated by respondents being "influenza", a virus detection test (such as the PCR test) is not commonly applied, as informed by the Acre state public health service. In consistency, the term "influenza-like illness" is used.) was the most frequently diagnosed disease, followed by pneumonia, suggesting that a health care-seeking rate below 40% may perpetuate health impairment and local contagion. Illnesses' severity, including the pain experienced, was the main predictor, revealing that subjective perception was more influential than objective individual and household characteristics. Conclusions The results suggest that subjective underestimation of respiratory illnesses' consequences for oneself and for local society could prevent health care from being sought. This is in line with some previous studies but departs from those emphasizing the role of objective factors. Social consequences, of, for instance, a macroeconomic nature, need to be highlighted based on studies detecting long-run relationships among health care demand, health and economic performance at the national level. Depending on the intensity of the trade-off between the costs imposed on the health system by increased demand and on the economy by the reduced productivity of the ill, policy could be adopted to change subjective perceptions of illnesses with nudges and educational and informational interventions.